2002
DOI: 10.1023/a:1021144729837
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The present systematic classification of Eriophyoidea is widely recognised as artificial and not reflecting plant-herbivore linkage. Quantitative description of host-related morphological variation can provide the basic information needed to improve the eriophyoid taxonomic system and enhance our understanding of mechanisms generating this variation. The purpose of this study was to investigate quantitative morphological traits of populations of cereal rust mite Abacarus hystrix (Nalepa 1896) living on differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 42 publications
(16 citation statements)
references
References 3 publications
0
15
0
1
Order By: Relevance
“…Additionally, the mite has a capacity for rapid population growth and can build up to very high densities (Skoracka and Kuczyński 2004), what may boost mites' dispersal and infestation of new grass hosts (Sabelis and Bruin 1996). Morphological examination of the cereal rust mite populations originating from three grass species (quackgrass, ryegrass and smooth brome) demonstrated that there is an apparent and discontinuous variation of body shape, length of setae and overall body size among host-associated mite populations (Skoracka et al 2002), which could be explained by a phenotypic adaptation to the local host environment (Pegler et al 2005), or might indicate partial or total genetic separation (host races or species) (Drès and Mallet 2002). Further studies revealed that quackgrass-and ryegrassassociated populations differ significantly in performance and acceptance of each other's hosts.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, the mite has a capacity for rapid population growth and can build up to very high densities (Skoracka and Kuczyński 2004), what may boost mites' dispersal and infestation of new grass hosts (Sabelis and Bruin 1996). Morphological examination of the cereal rust mite populations originating from three grass species (quackgrass, ryegrass and smooth brome) demonstrated that there is an apparent and discontinuous variation of body shape, length of setae and overall body size among host-associated mite populations (Skoracka et al 2002), which could be explained by a phenotypic adaptation to the local host environment (Pegler et al 2005), or might indicate partial or total genetic separation (host races or species) (Drès and Mallet 2002). Further studies revealed that quackgrass-and ryegrassassociated populations differ significantly in performance and acceptance of each other's hosts.…”
Section: Introductionmentioning
confidence: 99%
“…As the result of this integrative approach, which included genetic and morphometric analyses, host performance and preference tests, and reciprocal crosses, the population associated with ryegrass has been described as a new species Abacarus lolii Skoracka, a cryptic species of A. hystrix sensu lato (Skoracka 2009). Apart from the quackgrass and ryegrass populations of the cereal rust mite complex, morphometric and genetic studies included also the third population, which inhabited smooth brome (Skoracka et al 2002;Skoracka and Dabert 2010). The analyses revealed significant discontinuous morphological variation between these three host-associated populations (Skoracka et al 2002), which corresponded to an interspecific level of genetic variation in mtDNA COI (> 22%) (Skoracka and Dabert 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In both cases, A. davidmansoni can be clearly distinguished from A. genistae qualitatively by the pattern on the prodorsal shield and quantitatively by several characters such as the number of annuli on the hysterosoma (Xue et al 2015; Table 1 of this paper). Specialist herbivores such as eriophyid mites show strong host-dependent morphological variation in adaptation to different host species and environmental conditions (Skoracka et al 2002). For example, Skoracka et al (2014) reported that some characters (the length of the c2 setae, the number of dorsal annuli, and the length of chelicerae) could differentiate host-related species of eriophyoid mites (between the DBM and MT-1 genotypes), resolving the previous taxonomic confusion between wheat curl mite (Aceria tosichella) and dry bulb mite (Aceria tulipae).…”
Section: Discussion On Host Relationshipsmentioning
confidence: 99%
“…Studies have shown that arthropod populations may experience morphological variations along their geographical distribution (Saunders 1982). In eriophyid mites, cases of morphological variation have been associated with host specificity, and certain studies have shown that the involved characters very according to the structure of the host plant (Skoracka et al 2002). Studies with Euseius mesembrinus (Dean), a mite of the Phytoseiidae family, attributed the morphological variations observed in populations from Florida and Texas (USA) to geographical or nutritional factors because the morphological variations were verified only in field specimens, whereas in the laboratory under conditions in which food resources and other ecological factors were controlled, the variations did not occur (Abou-Setta et al 1991).…”
Section: Discussionmentioning
confidence: 99%